Zirconia hollow microspheres, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202611348231.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
然而目前的金属基吸附剂不能兼顾回收简便性与脱氟高效性
[0049]提供的氧化锆空心微球对含氟盐酸表现出优异的脱氟性能,饱和吸附容量>350mg/g,可在15min内达到吸附平衡,10次循环后再生率≥70%、锆浸出率≤0.5%,且仅需静置或常压过滤即可快速固液分离,有效解决了纳米吸附剂易团聚、难回收的问题,具有优异的工业应用前景。
Smart Images

Figure CN122999164A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adsorption materials technology, and relates to zirconia hollow microspheres, their preparation methods, and applications. Background Technology
[0002] Fluorinated hydrochloric acid is a common byproduct generated during the production processes of industries such as fluorochemicals, semiconductor manufacturing, electroplating, and photovoltaics. It typically consists of 10%–30% hydrochloric acid and fluorides with a concentration of 50–5000 ppm. According to the standard "By-product Hydrochloric Acid" (HG / T 3783-2021) and industry-standard quality requirements, the fluorine content in qualified by-product hydrochloric acid must not exceed 50 ppm. However, the fluorine concentration in fluorinated hydrochloric acid often exceeds the standard limit by tens to hundreds of times, reducing its quality and making it unusable for resource recovery. Therefore, developing efficient and economical defluorination technologies to purify fluorinated hydrochloric acid has become a key issue restricting the green and sustainable development of the industry.
[0003] Currently, water defluoridation methods mainly include precipitation, ion exchange, membrane separation, and adsorption. Among them, adsorption is widely considered one of the most promising defluoridation technologies due to its simple operation, high treatment efficiency, environmental friendliness, and lack of secondary pollution. The key to this technology lies in the rational selection and design of the adsorbent.
[0004] Based on their composition and properties, fluoride removal adsorbents can be broadly classified into two categories: non-metallic and metallic. Non-metallic adsorbents, represented by carbon-based materials, natural minerals, and biomass materials, are widely available and inexpensive, but their adsorption capacity is limited and they are easily affected by coexisting ions. Metallic adsorbents have surfaces rich in coordinate-unsaturated metal ions, which, as Lewis acid centers, can accept lone pairs of electrons from Lewis bases. Fluoride ions, as typical strong Lewis bases, form stable coordinate bonds with the empty orbitals of metal ions through their lone pairs of electrons. According to the hard and soft acid-base theory, Zr... 4+ hard acid and F - Hard bases exhibit high selectivity and affinity, while Cl... - With Zr 4+ The binding of chloride ions is relatively weak. Therefore, in the hydrochloric acid system, although a large number of chloride ions are present, fluoride ions have a stronger electron-donating ability and less steric hindrance, giving them an advantage in competitive coordination and thus achieving selective capture of fluoride ions. However, current metal-based adsorbents cannot simultaneously achieve both ease of recovery and high efficiency in defluorination. Summary of the Invention
[0005] Therefore, it is necessary to provide a method for preparing and applying zirconia hollow microspheres that can balance ease of recovery with high efficiency of defluorination.
[0006] In some embodiments, a method for preparing zirconia hollow microspheres is provided, comprising the following steps:
[0007] The zirconium source was mixed with ethanol to prepare the first mixture;
[0008] The first mixture is mixed with urea to prepare a second mixture;
[0009] The second mixture is mixed with an acidic aqueous solution and subjected to a solvothermal reaction under high pressure. Solid-liquid separation is performed, the solid phase is collected, washed, and dried to prepare the zirconium oxide hollow microspheres. The pressure of the solvothermal reaction is 1.0 MPa to 2.0 MPa, the temperature is 150°C to 180°C, and the time is 12 h to 24 h.
[0010] The zirconia hollow microspheres include a shell layer formed by the self-assembly of nanoparticles, the nanoparticles being monoclinic zirconia, and the shell layer having intergranular mesopores. The average particle size of the zirconia hollow microspheres is 2 μm to 5 μm, and the specific surface area of the zirconia hollow microspheres is 92.56 m². 2 / g~118.06m 2 / g.
[0011] In some embodiments, the provided method for preparing zirconia hollow microspheres satisfies one or more of the following conditions:
[0012] (1) The zirconium source comprises one or more of zirconium oxychloride, zirconium sulfate, and zirconium nitrate;
[0013] (2) The mass-to-volume ratio of the zirconium source to the ethanol is (5~20) g: 100 mL;
[0014] (3) The molar ratio of the zirconium source to the urea is 1:(2~4).
[0015] In some embodiments, the provided method for preparing zirconia hollow microspheres satisfies one or more of the following conditions:
[0016] (1) The acid in the acidic aqueous solution includes hydrochloric acid;
[0017] (2) The mass fraction of acid in the acidic aqueous solution is 30%~40%;
[0018] (3) The volume ratio of the ethanol to the acid aqueous solution is 100:(10~30);
[0019] (4) The drying temperature is 50℃~80℃ and the drying time is 10h~20h.
[0020] In some embodiments, the provided method for preparing zirconia hollow microspheres satisfies one or more of the following conditions:
[0021] (1) The nanoparticles are spindle-shaped;
[0022] (2) The average particle size of the nanoparticles is 32 nm to 69 nm;
[0023] (3) The size of the interparticle mesopores is 2 nm to 103 nm;
[0024] (4) The hollow structure of the zirconium oxide hollow microspheres is open or closed;
[0025] (5) The X-ray diffraction pattern of the hollow zirconia microspheres shows characteristic diffraction peaks of monoclinic zirconia, including a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°; optionally, the full width at half maximum (FWHM) of the first, second, and third 2θ diffraction peaks is independently 14.49±0.2°.
[0026] (6) The hollow zirconia microspheres contain 85% to 90% zirconia by mass;
[0027] (7) The surface of the zirconia hollow microspheres has hydroxyl groups and Lewis acid sites; optionally, the mass percentage of the hydroxyl groups in the zirconia hollow microspheres is 4% to 6%, and the total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g.
[0028] In some embodiments, a zirconia hollow microsphere is provided, the zirconia hollow microsphere comprising a shell formed by the self-assembly of nanoparticles, the nanoparticles comprising monoclinic zirconia, the shell having intergranular mesopores, the average particle size of the zirconia hollow microsphere being 2 μm to 5 μm, and the specific surface area of the zirconia hollow microsphere being 92.56 m². 2 / g~118.06m 2 / g.
[0029] In some embodiments, the provided zirconia hollow microspheres satisfy one or more of the following conditions:
[0030] (1) Prepared by the preparation method described above;
[0031] (2) The nanoparticles are spindle-shaped;
[0032] (3) The average particle size of the nanoparticles is 32nm~69nm;
[0033] (4) The size of the interparticle mesopores is 2 nm to 103 nm;
[0034] (5) The hollow structure of the zirconia hollow microspheres is open or closed;
[0035] (6) The hollow zirconia microspheres contain 85% to 90% zirconia by mass;
[0036] (7) The surface of the zirconia hollow microspheres has hydroxyl groups and Lewis acid sites; optionally, the mass percentage of the hydroxyl groups in the zirconia hollow microspheres is 4% to 6%, and the total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g.
[0037] In some embodiments, the provided hollow zirconia microspheres exhibit characteristic diffraction peaks of monoclinic zirconia in their X-ray diffraction patterns. These characteristic diffraction peaks include a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°. Optionally, the full width at half maximum (FWHM) of each of the first, second, and third 2θ diffraction peaks is independently 14.49±0.2°.
[0038] In some embodiments, the zirconia hollow microspheres prepared by the above preparation method or the zirconia hollow microspheres are provided for use as a defluorination agent;
[0039] The applications include at least the application in the defluorination of fluorinated hydrochloric acid.
[0040] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, comprising the following steps:
[0041] Fluorinated hydrochloric acid is mixed with zirconia hollow microspheres prepared by the above preparation method or the zirconia hollow microspheres, and adsorption is performed to reduce the fluorine content in the fluorinated hydrochloric acid.
[0042] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, satisfying one or more of the following conditions:
[0043] (1) The mass concentration of hydrochloric acid in the fluorinated hydrochloric acid is 10%~30%;
[0044] (2) The concentration of fluorine in the fluorinated hydrochloric acid, expressed as a mass ratio, is 40 ppm to 5000 ppm;
[0045] (3) The adsorption temperature is 15℃~35℃, and the adsorption time is 1min~150min;
[0046] (4) The mass-to-volume ratio of the zirconium oxide hollow microspheres to the fluorinated hydrochloric acid is (0.1~10) g: 1 L;
[0047] (5) The method of defluorinating fluorine-containing hydrochloric acid also includes a step of desorbing and regenerating the fluorine-adsorbed zirconium hollow microspheres. The reagents used for desorption and regeneration include 0.1 mol / L to 0.5 mol / L Na2CO3 aqueous solution, 0.1 mol / L to 0.5 mol / L HCl aqueous solution or saturated NaCl aqueous solution.
[0048] In the aforementioned method for preparing zirconia hollow microspheres, urea is used as a mineralizing agent. The zirconium source and urea are dissolved in a mixed solution of anhydrous ethanol and an acid (such as hydrochloric acid). During the solvothermal reaction, the zirconium source hydrolyzes to generate amorphous hydrated zirconium hydroxide. Ethanol is then dehydrated in situ under acid catalysis to generate an ether soft template. The hydrated zirconium hydroxide is induced to self-assemble at the template interface through a solvothermal reaction to form a hollow spherical shell. No external template is required, making the process simple, green, and environmentally friendly. The prepared zirconia hollow microspheres have a stable structure and can be used for defluorination of fluorinated hydrochloric acid. They exhibit low zirconium leaching rates, a micro-nano hierarchical structure, and a shell composed of self-assembled nano-spindle-shaped particles, combining the advantages of easy recovery at the micron-scale and high activity at the nano-scale.
[0049] The provided zirconia hollow microspheres exhibit excellent defluorination performance for fluorinated hydrochloric acid, with a saturated adsorption capacity >350mg / g. They can reach adsorption equilibrium within 15min, and after 10 cycles, the regeneration rate is ≥70% and the zirconium leaching rate is ≤0.5%. Furthermore, they can achieve rapid solid-liquid separation simply by standing or filtration under normal pressure, effectively solving the problems of easy agglomeration and difficult recovery of nano-adsorbents, and have excellent prospects for industrial applications. Attached Figure Description
[0050] To more clearly illustrate the technical solutions in the embodiments and examples of this application, and to more completely understand this application and its beneficial effects, the accompanying drawings used in the description of the embodiments or examples will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of this application. Those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0051] Figure 1 Scanning electron microscope (SEM) images of the hollow zirconia spheres obtained in Examples 1-4;
[0052] Figure 2 The images show the X-ray diffraction (XRD) patterns of the hollow zirconia spheres obtained in Examples 1-4, where "intensity" refers to "diffraction intensity" and "degree" refers to "diffraction angle".
[0053] Figure 3The N2 adsorption-desorption isotherms and pore size distribution curves of the zirconia hollow spheres obtained in Examples 1-4 are shown. In this figure, “Volume Adsorbed” refers to “adsorption volume”, “Relative Pressure” refers to “relative pressure”, and “PoreDiameter” refers to “pore size distribution”.
[0054] Figure 4 The image shows the ammonia-programmed temperature desorption (NH3-TPD) spectrum of the zirconia hollow spheres obtained in Example 1, where "signal" refers to "signal intensity", "weak" refers to "weak acid site", "middle" refers to "medium-strong acid site", and "strong" refers to "strong acid site".
[0055] Figure 5 The thermogravimetric analysis-differential scanning calorimetry (TG-DSC) curves of the zirconia hollow spheres obtained in Example 1 are shown below. In this data, “Weight” refers to “mass”, “Heat Flow” refers to “heat flow”, “TG curve” refers to “thermogravimetric curve”, and “DSC curve” refers to “differential scanning calorimetry curve”.
[0056] Figure 6 The adsorption isotherm of the zirconia hollow spheres obtained in Example 1 is shown below. "Experimental data" refers to "experimental measured data", "Langmuir" refers to "Langmuir model fitting curve (monolayer adsorption model)" and "Freundlich" refers to "Freundlich model fitting curve (multilayer empirical adsorption model)".
[0057] Figure 7 The image shows the adsorption kinetics curve fitting diagram of the hollow zirconia spheres obtained in Example 1. In this diagram, "Experimental data" refers to "experimental measured data", "Pseudo-first-order model" refers to "pseudo-first-order kinetic model", and "Pseudo-second-order model" refers to "pseudo-second-order kinetic model".
[0058] Figure 8 The diagram shows the cyclic regeneration performance of the zirconia hollow spheres obtained in Example 1, where "Regeneration rate" refers to the "regeneration rate" and "Cycle numbers" refers to the "number of cycles".
[0059] Figure 9 The graph shows the Zr leaching rate during the cycling process of the hollow zirconium spheres obtained in Example 1, where "Leaching rate of Zr" refers to the "leaching rate of zirconium" and "Cycle numbers" refers to the "number of cycles".
[0060] Figure 10 The image shows a comparison of the XRD patterns of the zirconia hollow spheres obtained in Example 1 before and after 10 cycles. In this image, "10 Cycle" means "10 cycles", "Fresh" means "no hydrochloric acid defluorination", "intensity" means "diffraction intensity", and "degree" means "diffraction angle".
[0061] Figure 11 The image shows the SEM image of the zirconia hollow spheres obtained in Example 1 after 10 cycles.
[0062] Figure 12 The figure shows the defluorination performance of hollow zirconium oxide spheres obtained under different solvothermal conditions, where "Adsorption efficiency" refers to the adsorption efficiency.
[0063] Figure 13 The diagram shows the defluorination performance results for some embodiments, where "Adsorption efficiency" refers to the adsorption efficiency. Detailed Implementation
[0064] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.
[0065] It should be noted that when a component is said to be "fixed to" another component, it can be directly attached to the other component or there may be an intervening component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there may be an intervening component.
[0066] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0067] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings:
[0068] The terms "and / or," "or / and," and "and / or" as used in this application encompass any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that in this application, the technical solution undoubtedly includes technical solutions connected by "logical AND," and also undoubtedly includes technical solutions connected by "logical OR." For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B."
[0069] In this application, the terms "multiple", "various", "multiple times", "multi-dimensional", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or more than or equal to two.
[0070] The terms “combinations thereof,” “any combination thereof,” and “any combination thereof” as used in this application include all suitable combinations of any two or more of the listed items.
[0071] In this application, the term "suitable" as used in "suitable combination", "suitable method", "any suitable method", etc., refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.
[0072] In this application, terms such as "preferred," "better," "more suitable," and "ideal" are merely used to describe implementation methods or embodiments that achieve better results, and should be understood not to limit the scope of protection of this application.
[0073] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes and to indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0074] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0075] In this invention, the terms "first aspect," "second aspect," "third aspect," and "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," and "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0076] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0077] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the selected numerical distributions within the aforementioned numerical intervals are considered continuous and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. In this document, this is equivalent to directly listing every integer. For example, if t is an integer selected from 1 to 10, it means that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0078] Unless otherwise specified, the temperature parameters in this application are permitted to be either constant-temperature treatment or variations within a certain temperature range. It should be understood that the constant-temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.
[0079] In this application, % (w / w) and wt% both represent weight percentage, % (v / v) refers to volume percentage, and % (w / v) refers to mass-volume percentage.
[0080] In this application, "room temperature" generally refers to 5℃~30℃, and more preferably 25±5℃.
[0081] Metal-based adsorbents, such as metal oxides or hydroxides like Al, Fe, Zr, Ce, and La, possess abundant Lewis acid sites on their surfaces. While alumina offers significant cost advantages, it is prone to severe structural collapse and aluminum ion leaching in strong acid environments, making it unsuitable for fluoride-containing hydrochloric acid systems. In contrast, zirconium oxide exhibits strong stability in hydrochloric acid. As a hard Lewis acid, its surface boasts abundant active sites and a high affinity for fluorides, making it the preferred defluorination adsorbent for strong acid systems. Doping zirconium-based materials with aluminum, lanthanum, or other composite components to enhance performance typically requires calcination above 800°C to obtain stable products. The preparation process for such materials is complex, costly, and energy-intensive. Furthermore, the doped metal elements pose a risk of leaching in strong acid systems, potentially causing secondary pollution to the treatment system.
[0082] Single-component zirconia has advantages such as simple composition, controllable structure, and low cost. However, traditional nano-zirconia is prone to agglomeration, and solid-liquid separation usually relies on centrifugation, which greatly limits its large-scale application. While simply increasing the particle size is beneficial for solid-liquid separation, it often comes at the cost of sacrificing specific surface area, leading to a reduction in active sites and a decrease in adsorption performance.
[0083] In some embodiments, a method for preparing zirconia hollow microspheres is provided, comprising the following steps:
[0084] The zirconium source was mixed with ethanol to prepare the first mixture;
[0085] The first mixture is mixed with urea to prepare the second mixture;
[0086] The second mixture was mixed with an acidic aqueous solution and subjected to a solvothermal reaction under high pressure. Solid-liquid separation was performed, the solid phase was collected, washed, and dried to prepare zirconia hollow microspheres. The pressure of the solvothermal reaction was 1.0 MPa to 2.0 MPa, the temperature was 150℃ to 180℃, and the time was 12h to 24h.
[0087] The zirconia hollow microspheres consist of a shell formed by the self-assembly of nanoparticles, including monoclinic zirconia. The shell has intergranular mesopores. The average particle size of the zirconia hollow microspheres is 2 μm to 5 μm, and the specific surface area of the zirconia hollow microspheres is 92.56 m². 2 / g~118.06m 2 / g.
[0088] In a non-limiting manner, during the solvothermal reaction, the zirconium source hydrolyzes to generate amorphous hydrated zirconium hydroxide (ZrO(OH)2·xH2O), which is then deposited and assembled at the interface of the ether oil droplet soft template, and further dehydrated and crystallized to finally directly generate monoclinic phase zirconium oxide hollow microspheres.
[0089] The provided preparation method yields zirconia hollow microspheres with a self-assembled shell, providing numerous exposed crystal faces that can form coordination bonds with fluorides; the hollow structure and intergranular mesopores provide rapid diffusion channels, making it easy for fluorides to access the active sites.
[0090] In some embodiments, the method for preparing zirconia hollow microspheres does not include a calcination step.
[0091] Without high-temperature calcination, abundant surface hydroxyl groups can be retained for ligand formation, which is beneficial for fluoride removal. High-temperature calcination will destroy these hydroxyl groups, reducing their content, making them more prone to aggregation, increasing particle size, and potentially causing the collapse of the micro-nano hierarchical structure, all of which will reduce adsorption performance.
[0092] In some embodiments, the provided method for preparing zirconia hollow microspheres uses a zirconium source comprising one or more of zirconium oxychloride, zirconium sulfate, and zirconium nitrate.
[0093] In some embodiments, the method for preparing zirconia hollow microspheres provides a mass-volume ratio of zirconium source to ethanol of (5~20) g:100 mL, for example, 5 g:100 mL, 10 g:100 mL, 15 g:100 mL, 20 g:100 mL, etc., or any range of the two aforementioned ratios.
[0094] In some embodiments, the method for preparing zirconia hollow microspheres provides a molar ratio of zirconium source to urea of 1:(2~4), for example, 1:2, 1:3, 1:4, etc., or any range of the two aforementioned ratios.
[0095] In some embodiments, the acid in the provided method for preparing zirconia hollow microspheres includes hydrochloric acid.
[0096] In some embodiments, the provided method for preparing zirconia hollow microspheres uses an acid aqueous solution with a mass fraction of 30% to 40%, for example, 30%, 35%, 40%, or any combination of the aforementioned values.
[0097] In some embodiments, the provided method for preparing zirconia hollow microspheres uses a volume ratio of ethanol to acid aqueous solution of 100:(10~30), for example, 100:10, 100:20, 100:30, etc., or any range of the two aforementioned ratios.
[0098] In some embodiments, the method for preparing zirconia hollow microspheres involves drying at a temperature of 50°C to 80°C and for a drying time of 10h to 20h. For example, the temperature can be 50°C, 60°C, 70°C, 80°C, etc., and the time can be 10h, 15h, 20h, etc. The values of temperature and time can also be ranges composed of any two of the aforementioned values.
[0099] In some embodiments, the provided method for preparing zirconia hollow microspheres uses spindle-shaped nanoparticles.
[0100] In some embodiments, the method for preparing zirconia hollow microspheres provides that the average particle size of the nanoparticles is 32nm~69nm, for example, 32nm, 40nm, 50nm, 60nm, 69nm, etc., or it can be a range composed of any two of the aforementioned values.
[0101] In some embodiments, the provided method for preparing zirconia hollow microspheres has mesopores with a size of 2 nm to 103 nm, such as 2 nm, 10 nm, 30 nm, 50 nm, 80 nm, 103 nm, etc., or any range of the aforementioned two values.
[0102] In some embodiments, the provided method for preparing zirconia hollow microspheres provides that the average particle size of the zirconia hollow microspheres is 2μm to 5μm, for example, 2μm, 3μm, 4μm, 5μm, etc., or it can be a range composed of any two of the aforementioned values.
[0103] In some embodiments, the provided method for preparing zirconia hollow microspheres shows characteristic diffraction peaks of monoclinic zirconia in the X-ray diffraction pattern of the zirconia hollow microspheres. The characteristic diffraction peaks of monoclinic zirconia include a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°. Optionally, the full width at half maximum (FWHM) of the first, second, and third 2θ diffraction peaks is 14.49±0.2°.
[0104] In some embodiments, the provided method for preparing zirconia hollow microspheres contains 85% to 90% zirconia by mass.
[0105] In some embodiments, the provided method for preparing zirconia hollow microspheres provides that the surface of the zirconia hollow microspheres has hydroxyl groups and Lewis acid sites.
[0106] In some embodiments, the hydroxyl groups in the zirconia hollow microspheres account for 4% to 6% by mass, and the total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g.
[0107] Lewis acidic sites are active sites that can accept electron pairs.
[0108] In some embodiments, the provided method for preparing zirconia hollow microspheres provides that the hollow structure of the zirconia hollow microspheres is open or closed.
[0109] In a non-limiting sense, the degree of shell opening can be controlled by adjusting the solvothermal temperature and time.
[0110] In some implementations, solid-liquid separation is performed after the solvothermal treatment reaction is completed and the mixture is cooled to room temperature.
[0111] In some implementations, the washing step involves alternating washing with ethanol and deionized water.
[0112] Secondly, in some embodiments, a zirconia hollow microsphere is provided, comprising a shell formed by the self-assembly of nanoparticles, the nanoparticles comprising monoclinic zirconia, the shell having intergranular mesopores, the average particle size of the zirconia hollow microsphere being 2 μm to 5 μm, and the specific surface area of the zirconia hollow microsphere being 92.56 m². 2 / g~118.06m 2 / g.
[0113] In some embodiments, the provided zirconia hollow microspheres are prepared by the aforementioned preparation method.
[0114] In some embodiments, the provided zirconium oxide hollow microspheres have spindle-shaped nanoparticles.
[0115] In some embodiments, the provided zirconia hollow microspheres have an average particle size of 32nm to 69nm, for example, 32nm, 40nm, 50nm, 60nm, 69nm, etc., or can be a range composed of any two of the aforementioned values.
[0116] In some embodiments, the provided zirconia hollow microspheres have interparticle mesopore sizes of 2 nm to 103 nm, such as 2 nm, 10 nm, 30 nm, 50 nm, 80 nm, 103 nm, etc., or can be a range composed of any two of the aforementioned values.
[0117] In some embodiments, the provided zirconia hollow microspheres have an average particle size of 2μm to 5μm, for example, 2μm, 3μm, 4μm, 5μm, etc., or can be a range composed of any two of the aforementioned values.
[0118] In some embodiments, the provided zirconia hollow microspheres contain 85% to 90% zirconia by mass.
[0119] In some embodiments, the provided zirconia hollow microspheres have hydroxyl groups and Lewis acid sites on their surface. The mass percentage of hydroxyl groups in the zirconia hollow microspheres is 4% to 6%, for example, 4%, 5%, 6%, etc., or any range of the aforementioned two values. The total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g, for example, 1.6 mmol / g, 1.7 mmol / g, 1.8 mmol / g, etc., or any range of the aforementioned two values.
[0120] In some embodiments, the provided zirconia hollow microspheres have an open or closed hollow structure.
[0121] In some embodiments, the provided hollow zirconia microspheres exhibit characteristic diffraction peaks of monoclinic zirconia in their X-ray diffraction patterns. These characteristic diffraction peaks include a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°. Optionally, the full width at half maximum (FWHM) of the first, second, and third 2θ diffraction peaks is 14.49±0.2°.
[0122] Thirdly, in some embodiments, the zirconia hollow microspheres prepared by the aforementioned preparation method or the aforementioned zirconia hollow microspheres are provided as defluorinating agents;
[0123] Applications include at least those used in the defluorination of fluorinated hydrochloric acid.
[0124] Fourthly, in some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, comprising the following steps:
[0125] Fluorinated hydrochloric acid is mixed with zirconia hollow microspheres prepared by the aforementioned method or the aforementioned zirconia hollow microspheres, and adsorption is performed to reduce the fluorine content in the fluorinated hydrochloric acid.
[0126] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, wherein the mass concentration of hydrochloric acid in the fluorinated hydrochloric acid is 10% to 30%, for example, 10%, 15%, 20%, 25%, 30%, etc., or it can be a range composed of any two of the aforementioned values.
[0127] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, wherein the concentration of fluorine in the fluorinated hydrochloric acid, by mass ratio, is 40ppm to 5000ppm, for example, 40ppm, 100ppm, 500ppm, 1000ppm, 2000ppm, 5000ppm, etc., or may be a range composed of any two of the aforementioned values.
[0128] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, wherein the adsorption temperature is 15℃~35℃ and the adsorption time is 1min~150min; for example, the temperature can be 15℃, 20℃, 25℃, 30℃, 35℃, etc., and the time can be 1min, 30min, 60min, 90min, 120min, 150min, etc., and the values of temperature and time can also be ranges composed of any two of the aforementioned values.
[0129] In some embodiments, a method for defluorinating fluorinated hydrochloric acid is provided, wherein the mass-to-volume ratio of zirconia hollow microspheres to fluorinated hydrochloric acid is (0.1~10) g:1L, for example, 0.1g:1L, 0.5g:1L, 1g:1L, 5g:1L, 10g:1L, etc., or any range of the two aforementioned ratios.
[0130] In some embodiments, a method for defluorinating with fluorine-containing hydrochloric acid is provided. The method further includes a step of desorption and regeneration of the fluorine-adsorbed zirconia hollow microspheres. The reagents used for desorption and regeneration include a 0.1 mol / L to 0.5 mol / L Na2CO3 aqueous solution, a 0.1 mol / L to 0.5 mol / L HCl aqueous solution, or a saturated NaCl aqueous solution. For example, the concentration of the Na2CO3 aqueous solution can be 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, etc., and the concentration of the HCl aqueous solution can be 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, etc., or can be a range composed of any two of the aforementioned values.
[0131] The provided method for preparing zirconia hollow microspheres does not require elemental doping or high-temperature calcination, effectively avoiding the risk of leaching of dopant components in a strong acid environment. Furthermore, it is the first time that micro-nano hierarchical zirconia hollow microspheres have been applied to the defluorination treatment of fluorine-containing hydrochloric acid, filling a research gap in this technical field.
[0132] The provided zirconia hollow microspheres have abundant intergranular mesopores and an open hollow structure.
[0133] The following are specific embodiments. They are intended to provide a more detailed description of this application to help those skilled in the art and researchers better understand it. The technical conditions described do not constitute any limitation on this application. Any modifications made within the scope of the claims of this application are protected by the claims.
[0134] Unless otherwise stated, all raw materials and reagents used in the following examples are commercially available or can be prepared by known methods. Experimental methods not specifying particular conditions in the examples were performed under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.
[0135] The zirconium oxychloride octahydrate (ZrOCl2·8H2O) used in the following examples and comparative examples had a purity of 99% and was sourced from Shanghai Bid Pharmaceutical Technology Co., Ltd.; the urea (CH4N2O) was of analytical grade and was sourced from Tianjin Aopusheng Chemical Co., Ltd.
[0136] The preparation method of the nanoscale monoclinic ZrO2 (m-ZrO2) used is as follows:
[0137] First, 0.028 mol of zirconium oxychloride octahydrate was added to 100 mL of ultrapure water and stirred for 30 min. Then, 0.056 mol of urea was added, and the mixture was stirred continuously for 60 min. 70 mL of the mixture was then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated at 150 °C for 12 h. After cooling to room temperature, the precipitate was dialyzed for 72 h and collected. The precipitate was then dried at 60 °C for 12 h, and the resulting sample was labeled as m-ZrO2.
[0138] Example 1
[0139] At room temperature, 9.03 g of zirconium oxychloride octahydrate was dissolved in 100 mL of anhydrous ethanol and stirred for 30 min until completely dissolved. 3.36 g of urea was added and stirring was continued for 60 min. 20 mL of 36% hydrochloric acid was added and stirred for 30 min, at which point the solution became clear. 45 mL of the above mixed solution was transferred to a 100 mL Teflon-lined high-pressure reactor and solvated at 1 MPa and 150 °C for 18 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. The precipitate was then dried at 60 °C for 12 h to obtain a white powder product.
[0140] Example 2
[0141] At room temperature, 9.03 g of zirconium oxychloride octahydrate was dissolved in 100 mL of anhydrous ethanol and stirred for 30 min until completely dissolved. 3.36 g of urea was added and stirring was continued for 60 min. 20 mL of 36% hydrochloric acid was added and stirred for 30 min, at which point the solution became clear. 45 mL of the above mixed solution was transferred to a 100 mL Teflon-lined high-pressure reactor and solvated at 1 MPa and 150 °C for 24 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to stand to allow the precipitate to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. It was then dried at 60 °C for 12 h to obtain a white powder product.
[0142] Example 3
[0143] At room temperature, 9.03 g of zirconium oxychloride octahydrate was dissolved in 100 mL of anhydrous ethanol and stirred for 30 min until completely dissolved. 3.36 g of urea was added and stirring was continued for 60 min. 20 mL of 36% hydrochloric acid was added and stirred for 30 min, at which point the solution became clear. 45 mL of the above mixed solution was transferred to a 100 mL Teflon-lined high-pressure reactor and solvothermal treated at 1.2 MPa and 160 °C for 18 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. It was then dried at 60 °C for 12 h to obtain a white powder product.
[0144] Example 4
[0145] At room temperature, 9.03 g of zirconium oxychloride octahydrate was dissolved in 100 mL of anhydrous ethanol and stirred for 30 min until completely dissolved. 3.36 g of urea was added and stirring was continued for 60 min. 20 mL of 36% hydrochloric acid was added and stirred for 30 min, at which point the solution became clear. 45 mL of the above mixed solution was transferred to a 100 mL Teflon-lined high-pressure reactor and solvothermal treated at 1.2 MPa and 180 °C for 18 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. The precipitate was then dried at 60 °C for 12 h to obtain a white powder product.
[0146] Example 5
[0147] This embodiment provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 1, except that the solvothermal treatment time in this comparative example is 12 hours. The remaining steps and parameter settings are the same as in Example 1.
[0148] Example 6
[0149] This embodiment provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 3, except that the solvothermal treatment time in this comparative example is 12 hours. The remaining steps and parameter settings are the same as in Example 3.
[0150] Example 7
[0151] This embodiment provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 3, except that the solvothermal treatment time in this comparative example is 24 hours. The remaining steps and parameter settings are the same as in Example 3.
[0152] Example 8
[0153] This embodiment provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 4, except that the solvothermal treatment time in this comparative example is 12 hours. The remaining steps and parameter settings are the same as in Example 4.
[0154] Example 9
[0155] This embodiment provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 4, except that the solvothermal treatment time in this comparative example is 24 hours. The remaining steps and parameter settings are the same as in Example 4.
[0156] Example 10
[0157] This comparative example provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 1, except that in this comparative example, the microspheres are dried at 100°C for 12 hours. The remaining steps and parameter settings are the same as in Example 1.
[0158] Comparative Example 1
[0159] This comparative example provides a zirconia hollow microsphere, the preparation method of which is similar to that of Example 1, except that in this comparative example, the dried white powder product is calcined at 1000°C for 2 hours. The remaining steps and parameter settings are the same as in Example 1.
[0160] Comparative Example 2
[0161] This comparative example provides a zirconium oxide hollow microsphere, the preparation method of which is as follows:
[0162] At room temperature, 3g of aluminum nitrate nonahydrate and 9.03g of zirconium oxychloride octahydrate were dissolved in 100mL of anhydrous ethanol and stirred for 30min until completely dissolved. 3.36g of urea was added and stirring was continued for 60min. 20mL of 36% hydrochloric acid was added and stirred for 30min until the solution became clear. 45mL of the above mixed solution was transferred to a 100mL Teflon-lined high-pressure reactor and solvothermal treated at 150℃ for 18h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. The precipitate was then dried at 60℃ for 12h to obtain a powdered product.
[0163] The obtained powdered product was calcined at 1000℃ for 2 hours.
[0164] Comparative Example 3
[0165] This comparative example provides a zirconium oxide hollow microsphere, the preparation method of which is as follows:
[0166] At room temperature, 17.32 g of lanthanum nitrate hexahydrate and 9.03 g of zirconium oxychloride octahydrate were dissolved in 100 mL of anhydrous ethanol and stirred for 30 min until completely dissolved. 3.36 g of urea was added and stirring was continued for 60 min. 20 mL of 36% hydrochloric acid was added and stirred for 30 min, at which point the solution became clear. 45 mL of the above mixed solution was transferred to a 100 mL Teflon-lined high-pressure reactor and solvothermal treated at 150 °C for 18 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and allowed to stand to allow the precipitate to settle. The supernatant was discarded, and the precipitate was washed three times alternately with anhydrous ethanol and deionized water. It was then dried at 60 °C for 12 h to obtain a powdered product.
[0167] The obtained powdered product was calcined at 1000℃ for 2 hours.
[0168] Characterization of zirconia hollow microspheres
[0169] The morphology of the obtained hollow zirconia microspheres was characterized using a Thermo Fisher Apreo S LoVac field emission scanning electron microscope (SEM), and the results are as follows: Figure 1 As shown. From Figure 1 As can be seen, the zirconium oxide hollow microspheres prepared in Examples 1 to 4 have a particle size of approximately 2 μm, exhibiting an open hollow spherical structure, with the shell formed by the self-assembly of nano-spindle-shaped particles. Figure 1 As can be seen, with the increase of temperature and the extension of time, the zirconia shell gradually becomes more complete, showing obvious structural evolution: In Example 1, the solvothermal reaction was carried out at 150℃ for 18 hours, and the prepared zirconia hollow microspheres showed obvious open structure with large openings in the shell; while in Example 2, after the reaction time was extended to 24 hours, only a few small pores remained on the surface of the zirconia hollow microspheres, and the integrity was significantly improved; in Example 3, when the temperature was raised to 160℃, although the obtained zirconia hollow microspheres had a few fragments, the shell was basically continuous; in Example 4, when the temperature was further raised to 180℃, the obtained zirconia hollow microspheres formed a continuous, dense, and complete shell without obvious gaps, and the structure was relatively regular.
[0170] The crystal phase composition of the samples was analyzed using a Rigaku D / max2500 powder X-ray diffractometer (Japan). A Cu target (λ = 0.15418 nm) was used, with a voltage of 40 kV and a current of 100 mA. Scanning was performed at a speed of 10° / min within the range of 20-80°. The XRD patterns of the obtained zirconia hollow microspheres were measured. The XRD patterns of the zirconia hollow microspheres prepared in Examples 1-4 are shown below. Figure 2 As shown. From Figure 2As can be seen, the prepared zirconia hollow microspheres have monoclinic phase characteristic peaks at 2θ of 24.04±0.2°, 28.05±0.2°, and 31.49±0.2°, with a half-width at half-maximum of 14.49±0.2°.
[0171] The specific surface area and pore structure of the samples were characterized using BET (Brunauer-Emmett-Teller) assay. In the pretreatment stage, equal amounts of four types of samples were dried in an oven at 60℃ for 12 h, followed by vacuum degassing at 150℃ for 6 h to remove physically adsorbed water and gases from the surface. Nitrogen adsorption-desorption was used for testing at 77 K, and the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method. The results are shown in the figure below. Figure 3 As shown in Table 1.
[0172] Table 1
[0173]
[0174] from Figure 3 As shown in Table 1, the intergranular mesopores of the provided zirconia hollow microspheres have a pore diameter of 2–103 nm and a specific surface area of 92.56 m². 2 / g~118.06m 2 / g.
[0175] The acid site distribution and acidity value on the sample surface were characterized using ammonia-programmed temperature desorption technology. The method is as follows: 100 mg of sample was weighed and placed in a reaction tube. The sample was pre-treated by drying at a programmed temperature increase from room temperature to 200 °C at 10 °C / min. The sample was then purged with a He gas flow of 30-50 mL / min for 1 h. After cooling to 50 °C, a 10% NH3 / He mixture was introduced for 1 h until saturation. The He gas flow was then switched to 30-50 mL / min for 1 h to remove the weakly physically adsorbed NH3 on the surface. Finally, the temperature was increased to 800 °C at a rate of 10 °C / min under a He atmosphere. The desorbed ammonia was continuously monitored and recorded using a thermal conductivity detector (TCD). The peak area was quantified using standards and used to calculate the surface acidity. The results are shown in the figure below. Figure 4 As shown, the specific acid content can be obtained by integrating the peak area. In Example 1, the total Lewis acid content is 1.692 mmol / g.
[0176] Thermogravimetric-Differential Scanning Calorimetry (TG-DSC) was used to assess the thermal stability, surface hydroxyl groups, and crystal phase composition of the material. 5-10 mg of sample was weighed and tested in a N2 atmosphere at a heating rate of 10 °C / min from room temperature to 500 °C. The results are as follows: Figure 5As shown, the total weight loss during the process of heating from room temperature to 500℃ at a heating rate of 10℃ / min in N2 atmosphere was about 12%, mainly due to the removal of adsorbed water, volatile components and hydroxyl groups. No obvious crystallization exothermic peak was observed in the temperature range of 400-500℃, proving that the obtained product is pure monoclinic zirconia and basically does not contain amorphous phase.
[0177] Test Example 1
[0178] The defluorination performance of the product obtained in Example 1 was tested using the following method:
[0179] Adsorption test: A certain amount of adsorbent is added to a conical flask containing fluorinated hydrochloric acid, and then placed in a shaker for adsorption. After adsorption is completed, solid and liquid are separated, the fluorine concentration of the defluorinated solution is tested, and the defluorination rate and adsorption capacity are calculated.
[0180] 1. Adsorption isotherm test
[0181] Test procedure: 2.0 g / L of zirconia hollow spheres were added to hydrochloric acid with different initial concentrations of fluoride (hydrochloric acid mass fraction of 20%, fluoride concentrations of 40, 70, 190, 500, 700, and 900 ppm), and the solutions were shaken for approximately 1 hour at 288.15 K, 298.15 K, and 308.15 K, respectively. After adsorption was complete, the remaining fluoride concentration of the solutions was measured, and the data were processed to derive isotherms.
[0182] Test results are as follows Figure 6 As shown, the saturated adsorption capacity of the material exhibits a trend of first decreasing and then increasing with increasing temperature. When the adsorption temperature increases from 15℃ to 25℃, the actual adsorption capacity drops to 118.79 mg / g, and the Langmuir saturated adsorption capacity is only 172.47 mg / g; however, when the temperature further increases to 35℃, the actual adsorption capacity rebounds, and the Langmuir saturated adsorption capacity reaches as high as 358.06 mg / g. This trend indicates that the adsorption of fluorides by the provided zirconia hollow microspheres is not dominated by a single mechanism, but is the result of the synergistic effect of physical adsorption and chemical adsorption. In the low-temperature range (15-25℃), physical adsorption dominates. Since physical adsorption is an exothermic process, the increase in temperature inhibits the electrostatic interaction between the fluoride and the adsorbent surface, leading to a decrease in adsorption capacity. As the temperature further increases, chemical adsorption gradually becomes dominant. At this point, the fluoride can overcome diffusion resistance and activation energy barriers, occupying the active sites on the ZrO2 surface. This process has endothermic characteristics, therefore, the increase in temperature promotes the adsorption reaction.
[0183] 2. Adsorption kinetics test
[0184] Test procedure: 3.5 g / L of zirconium oxide hollow spheres were added to fluorine-containing hydrochloric acid (hydrochloric acid mass fraction 20%, fluorine concentration 190 ppm), and the mixture was shaken and adsorbed in a shaker at 25 °C. The fluorine concentration of the defluorinated solution was measured at 10 s, 5 min, 10 min, 30 min, 45 min, 60 min and 90 min of adsorption.
[0185] Test results are as follows Figure 7 As shown. Figure 7 As shown in Figure A, the adsorbent reaches 66% of its saturated adsorption capacity within 10 seconds, indicating the presence of numerous readily accessible active sites on the material surface. The entire adsorption process reaches adsorption equilibrium within 15 minutes. This rapid adsorption behavior can be attributed to the abundant mesoporous structure of the hollow spherical shell, which provides unobstructed diffusion channels for fluorides and significantly shortens the mass transfer path.
[0186] like Figure 7 As shown in Figure B, to further elucidate the rate-controlling mechanism of the adsorption process, an intraparticle diffusion model was used to fit and analyze the kinetic data. The kinetic data (adsorption capacity Qe corresponding to different times t) were processed, with each point representing the experimental point (t, Qe) after setting t to t^0.5. The three lines are all fitted, corresponding to the three stages of adsorption. The results show that the adsorption process exhibits a typical three-stage linear characteristic. The first stage is the instantaneous adsorption stage, where fluoride diffuses from the bulk solution to the outer surface of the adsorbent, rapidly capturing surface active sites. The second stage is the intraparticle diffusion stage, which is the main rate-controlling step, with the adsorption rate dominated by the diffusion behavior of fluoride within the mesoporous channels. The third stage is the adsorption equilibrium stage, where the straight line is horizontal, indicating that adsorption has reached saturation and the adsorption-desorption dynamic equilibrium has been established.
[0187] 3. Desorption test
[0188] Test Procedure: The adsorbed material was washed with water and dried. Then, it was mixed with the desorption solution (0.1M sodium carbonate solution) at a mass ratio of 1 g:50 mL and desorbed at 30°C in a shaker for 30 min. The desorbed material was washed with water until neutral, dried, and then used for adsorption cycle testing, repeated 10 times. The zirconium oxide hollow microspheres were tested as follows: zirconium leaching rate was measured using inductively coupled plasma optical emission spectrometry (ICP-OES), crystal phase composition was analyzed using powder X-ray diffraction, and morphology was observed using scanning electron microscopy.
[0189] The method for detecting zirconium leaching rate using inductively coupled plasma atomic emission spectrometry (ICP-OES) is as follows: The adsorbed solution is passed through a 0.22-micron filter membrane, neutralized with saturated boric acid solution, and then the pH is adjusted to 6-7 using hydrochloric acid and sodium hydroxide solution. The treated sample solution is then introduced into an ICP-OES instrument to measure its emitted light intensity. Substituting this into a concentration-intensity standard curve, the zirconium concentration in the treated sample solution can be obtained. The zirconium concentration in the post-adsorption solution can then be calculated based on the dilution ratio.
[0190] The regeneration rate is calculated as follows: Regeneration rate Re = (Defluorination rate after n cycles / Initial defluorination rate) × 100%.
[0191] Test results are as follows Figures 8-11 As shown, the regeneration rate was above 90% in the first 5 cycles. After 10 cycles, the XRD peak position remained unchanged. A small amount of fragmentation appeared in the hollow spheres, but the overall spherical structure was still retained. The regeneration rate was >73%, and the zirconium leaching rate was ≤0.5%, indicating good cycle stability. The adsorption performance of the material could still maintain 73%, mainly due to the unique open hierarchical structure and abundant mesoporous channels of the hollow spheres, which allowed the alkaline solution to quickly enter the shell. At the same time, during the adsorption process, some fluorides formed stable complexes with the active sites on the zirconium oxide surface, which were difficult to completely desorb by alkaline washing, resulting in the loss of some effective active sites in the mesoporous structure.
[0192] Test Example 2
[0193] Equal weights of the zirconium oxide hollow microspheres prepared in the examples and comparative examples were added to equal amounts of fluorinated hydrochloric acid and subjected to shaking adsorption at room temperature.
[0194] Detection Method: The adsorbed solutions were filtered, and the fluoride concentration of the samples was determined using a fluoride ion-selective electrode (PF-2-01 type), referring to the People's Republic of China National Standard GB / T 7484-1987 "Determination of Fluoride in Water - Ion-Selective Electrode Method". This standard is widely applicable to the detection of fluoride in surface water, groundwater, and industrial wastewater. First, a series of standard fluoride solutions of known concentrations were prepared, and a total ionic strength adjustment buffer (TISAB) was added. The potential value (mV) was measured, and a standard curve of fluoride ion concentration (log c) was plotted. For sample determination, an appropriate amount of the supernatant after adsorption was taken, and an equal volume of TISAB was added. The solution was adjusted to pH 5-7 using acid and alkali, and the potential was measured before calculating the fluoride concentration using the standard curve. The original adsorption solution was in hydrochloric acid medium, where fluoride mainly existed in the form of HF. However, after adding TISAB and adjusting the pH, HF completely dissociated into fluoride. - Therefore, the response potential measured by this method still accurately corresponds to the fluoride concentration in the solution.
[0195] The detection results of Examples 1 to 10 are as follows: Figure 12 and Figure 13 As shown in the figure, the provided zirconia hollow microspheres exhibit high defluorination efficiency. However, the defluorination rates of the materials prepared in Comparative Examples 1 to 3 are all 0, indicating that high-temperature calcination renders the materials ineffective and unsuitable for removing fluoride from hydrochloric acid.
[0196] Test Example 3
[0197] To evaluate the solid-liquid separation performance of zirconia hollow microspheres, the filtration rate and filter cake moisture content were measured. The test methods are as follows:
[0198] A certain volume of the adsorption suspension was poured into a G4 sintered glass crucible. The total time required for the filtrate to completely pass through was recorded to calculate the filtration rate. After the filtrate had completely passed through, vacuum aspiration was continued for two minutes to remove any remaining free liquid in the filter cake. The resulting wet filter cake was then collected and weighed. The adsorption suspension contained zirconia hollow microspheres or nanoscale monoclinic ZrO2 (m-ZrO2) provided in this application for adsorbing fluoride from hydrochloric acid.
[0199] Relevant parameters and calculation formulas: Filtration rate indicates the ease with which the filtrate passes through the filter cake under gravity. A higher rate reflects better solid-liquid separation. Filter cake water content measures the amount of residual liquid after vacuum filtration; a lower value indicates more efficient liquid removal. The calculation methods for these parameters are as follows, see formulas (1) and (2):
[0200] (1);
[0201] (2);
[0202] Wherein, v(mL·min -1 V is the filtration rate, V (mL) is the filtrate volume, and t (s) is the total filtration time. θ (%) is the moisture content of the filter cake, m wet (g) and m dry (g) represents the mass of the wet filter cake after vacuum filtration and the mass of the filter cake after drying at 6°C for 24 hours.
[0203] Experimental Results and Analysis: The solid-liquid separation characteristics of the samples were studied through filtration performance experiments. Key parameters are summarized in Table 2 below. The results show that there are significant differences in performance between the two samples. Under the same experimental conditions, the filtration rate of Example 1 is approximately 3.35 times that of nano-sized monoclinic ZrO2. Meanwhile, the moisture content of the filter cake in Example 1 is slightly higher than that of nano-sized monoclinic ZrO2. This is attributed to the fact that the particles in Example 1 are significantly larger than the membrane pore size (0.45 μm), causing them to be completely trapped on the membrane surface, forming a highly porosity and loosely packed filter cake. Therefore, the filtration resistance is lower, resulting in a higher filtration rate. In contrast, the particles of nano-sized monoclinic ZrO2 are smaller than the membrane pore size. Some nanoparticles penetrate and block the internal pores of the membrane, while the remaining particles accumulate on the membrane surface, forming an extremely dense filter cake layer. These two effects together lead to a sharp increase in filtration resistance and a significant decrease in filtration rate.
[0204] Table 2 shows the key parameters of filtration performance between Example 1 and nano-sized ZrO2.
[0205]
[0206] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0207] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A method for preparing zirconia hollow microspheres, characterized in that, Includes the following steps: The zirconium source was mixed with ethanol to prepare the first mixture; The first mixture is mixed with urea to prepare a second mixture; The second mixture is mixed with an acidic aqueous solution and subjected to a solvothermal reaction under high pressure. Solid-liquid separation is performed, the solid phase is collected, washed, and dried to prepare the zirconium oxide hollow microspheres. The pressure of the solvothermal reaction is 1.0 MPa to 2.0 MPa, the temperature is 150°C to 180°C, and the time is 12 h to 24 h. The zirconia hollow microspheres include a shell layer formed by the self-assembly of nanoparticles, the nanoparticles being monoclinic zirconia, and the shell layer having intergranular mesopores. The average particle size of the zirconia hollow microspheres is 2 μm to 5 μm, and the specific surface area of the zirconia hollow microspheres is 92.56 m². 2 / g~118.06m 2 / g.
2. The method for preparing zirconia hollow microspheres according to claim 1, characterized in that, One or more of the following conditions must be met: (1) The zirconium source comprises one or more of zirconium oxychloride, zirconium sulfate, and zirconium nitrate; (2) The mass-to-volume ratio of the zirconium source to the ethanol is (5~20) g: 100 mL; (3) The molar ratio of the zirconium source to the urea is 1:(2~4).
3. The method for preparing zirconia hollow microspheres according to claim 1, characterized in that, One or more of the following conditions must be met: (1) The acid in the acidic aqueous solution includes hydrochloric acid; (2) The mass fraction of acid in the acidic aqueous solution is 30%~40%; (3) The volume ratio of the ethanol to the acid aqueous solution is 100:(10~30); (4) The drying temperature is 50℃~80℃ and the drying time is 10h~20h.
4. The method for preparing zirconia hollow microspheres according to any one of claims 1 to 3, characterized in that, One or more of the following conditions must be met: (1) The nanoparticles are spindle-shaped; (2) The average particle size of the nanoparticles is 32 nm to 69 nm; (3) The size of the interparticle mesopores is 2 nm to 103 nm; (4) The hollow structure of the zirconium oxide hollow microspheres is open or closed; (5) The X-ray diffraction pattern of the hollow zirconia microspheres shows characteristic diffraction peaks of monoclinic zirconia, including a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°; optionally, the full width at half maximum (FWHM) of the first, second, and third 2θ diffraction peaks is independently 14.49±0.2°. (6) The hollow zirconia microspheres contain 85% to 90% zirconia by mass; (7) The surface of the zirconium oxide hollow microspheres has hydroxyl groups and Lewis acid sites; Optionally, the hydroxyl groups in the zirconia hollow microspheres account for 4% to 6% by mass, and the total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g.
5. A type of hollow zirconium oxide microsphere, characterized in that, The zirconia hollow microspheres include a shell layer formed by the self-assembly of nanoparticles, the nanoparticles being monoclinic zirconia, and the shell layer having intergranular mesopores. The average particle size of the zirconia hollow microspheres is 2 μm to 5 μm, and the specific surface area of the zirconia hollow microspheres is 92.56 m². 2 / g~118.06m 2 / g.
6. The zirconia hollow microspheres according to claim 5, characterized in that, One or more of the following conditions must be met: (1) Prepared by the preparation method according to any one of claims 1 to 4; (2) The nanoparticles are spindle-shaped; (3) The average particle size of the nanoparticles is 32nm~69nm; (4) The size of the interparticle mesopores is 2 nm to 103 nm; (5) The hollow structure of the zirconia hollow microspheres is open or closed; (6) The hollow zirconia microspheres contain 85% to 90% zirconia by mass; (7) The surface of the zirconium oxide hollow microspheres has hydroxyl groups and Lewis acid sites; Optionally, the hydroxyl groups in the zirconia hollow microspheres account for 4% to 6% by mass, and the total Lewis acid content of the zirconia hollow microspheres is 1.6 mmol / g to 1.8 mmol / g.
7. The zirconia hollow microspheres according to claim 5 or 6, characterized in that, The X-ray diffraction pattern of the hollow zirconia microspheres shows characteristic diffraction peaks of monoclinic zirconia, including a first 2θ diffraction peak at 24.04±0.2°, a second 2θ diffraction peak at 28.05±0.2°, and a third 2θ diffraction peak at 31.49±0.2°; optionally, the full width at half maximum (FWHM) of the first, second, and third 2θ diffraction peaks is independently 14.49±0.2°.
8. The application of the zirconia hollow microspheres prepared by the preparation method according to any one of claims 1 to 4, or the zirconia hollow microspheres according to any one of claims 5 to 7, as a defluorinating agent; The applications include at least the application in the defluorination of fluorinated hydrochloric acid.
9. A method for defluorinating fluoride-containing hydrochloric acid, characterized in that, Includes the following steps: Fluorinated hydrochloric acid is mixed with zirconia hollow microspheres prepared by the preparation method according to any one of claims 1 to 4 or zirconia hollow microspheres according to any one of claims 5 to 7, and adsorption is performed to reduce the fluorine content in the fluorinated hydrochloric acid.
10. The method for defluorinating fluorinated hydrochloric acid according to claim 9, characterized in that, One or more of the following conditions must be met: (1) The mass concentration of hydrochloric acid in the fluorinated hydrochloric acid is 10%~30%; (2) The concentration of fluorine in the fluorinated hydrochloric acid, expressed as a mass ratio, is 40 ppm to 5000 ppm; (3) The adsorption temperature is 15℃~35℃, and the adsorption time is 1min~150min; (4) The mass-to-volume ratio of the zirconium oxide hollow microspheres to the fluorinated hydrochloric acid is (0.1~10) g: 1 L; (5) The method of defluorinating fluorine-containing hydrochloric acid also includes a step of desorbing and regenerating the fluorine-adsorbed zirconium hollow microspheres. The reagents used for desorption and regeneration include 0.1 mol / L to 0.5 mol / L Na2CO3 aqueous solution, 0.1 mol / L to 0.5 mol / L HCl aqueous solution or saturated NaCl aqueous solution.
